Pobór powszechny i armia narodowa: przegląd problematyki - Kilias, Jarosław (Studia Socjologiczno-Polityczne. Seria Nowa, 2018)
The paper deals with the conscription and the universal, compulsory military service. It presents it not as a groundbreaking novelty introduced by the French and American revolutionaries, but rather as a link in a chain of the development of various forms of a compulsory military service. In fact, it was far from universal, as it formed a burden that laid first and foremost on lower society classes. Only since the late XIX-th century it started to becoming truly universal, although the upper classes retained their privileged position in the military. In fact, variety of equality issues accompanied the conscription all over its whole existence. The paper also deals with the links, the supposed and real ones, which relate the conscription to the development of citizenship and democracy. It also touches upon the issue of the military usefulness of this recruitment form, compared to its alternatives, such as all-volunteer force, mercenary or militia.